2018
DOI: 10.29011/2574-7754/100065
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recalcitrant Medial Clavicle Non-union with Novel Dual Plating Technique

Abstract: Medial clavicle fracture are rare injuries associated with significant morbidity. Treated conservatively historically, operative management has been recommended to improve function and union rates. Optimal surgical fixation has not been described, particularly in revision cases following failed fixation. Previously described options include sternoclavicular fusion or partial claviculectomy. We describe a case of a 33-year-old female surgeon who had two failed surgeries treated with iliac crest tricortical graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Some authors suggested wire fixation, T-plate fixation, or advice for or against plating across the SC joint, all with varying outcomes. 2 , 3 , 5 , 13 , 19 Some noted drawbacks of plating across the SC joint are that the plate is subject to high torsion forces during shoulder motion and that another procedure is required to remove the hardware and restore motion. 2 , 13 , 19 However, locking plate fixation has produced good results when fixation over the sternum is a necessity, especially when compared to utilization of a nonlocking system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors suggested wire fixation, T-plate fixation, or advice for or against plating across the SC joint, all with varying outcomes. 2 , 3 , 5 , 13 , 19 Some noted drawbacks of plating across the SC joint are that the plate is subject to high torsion forces during shoulder motion and that another procedure is required to remove the hardware and restore motion. 2 , 13 , 19 However, locking plate fixation has produced good results when fixation over the sternum is a necessity, especially when compared to utilization of a nonlocking system.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 5 , 13 , 19 Some noted drawbacks of plating across the SC joint are that the plate is subject to high torsion forces during shoulder motion and that another procedure is required to remove the hardware and restore motion. 2 , 13 , 19 However, locking plate fixation has produced good results when fixation over the sternum is a necessity, especially when compared to utilization of a nonlocking system. 13 As described here, fixation across the SC joint with a reversed distal clavicle locking plate can be considered as a possible option when medial fracture fragment size precludes potential fixation in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation